Hubungan Antara Tingkat Stres Dengan Dismenore Pada Siswi Kelas Tiga SMK Batik 1 Surakarta - Berlianawati, Nur Anadya (2016)
Stress is the body's reaction or response to psychosocial stressors ( mental stress or load life ). Whereas on dysmenorrhea is the leading cause of school absenteeism and one of the causes of restrictions on activities of daily living, social interaction, decreased work efficiency and quality of life. Psychological factors (stress) is one of the factors that cause dysmenorrhea. Objective : This research purpose to know is there a correlation between stress levels with dysmenorrhea in third grade students of SMK Batik 1 Surakarta. Method : This study was an observational study with cross sectional analytic. Subjects were third grade SMK Batik 1 Surakarta. The total sample of 130 students. Sampling with total sampling technique. Measuring instrument used was PSS-10 (Perceived Stress Scale), which consists of 10 questions and the questionnaire Universal Pain Assessment Tool. Data were analyzed by Chi-Square. Result : The results obtained in this study using Chi-Square p value of 0.000 means that there is a significant relationship between the level of stress with dysmenorrhea in third grade SMK Batik 1 Surakarta. Conclusion : There is a significant correlation between stress levels with dysmenorrhea in third grade students of SMK Batik 1 Surakarta.